PPIH associated with immune infiltrates and immunotherapy response in hepatocellular carcinoma - Haini Chen; Haixia Chen; Renjie Wang; Peng Ren; Jun Ye (European Journal of Inflammation)
Background: The role of Ppih in immune infiltration and its response to immunotherapy in hepatocellular carcinoma (HCC) patients has not yet been investigated. Methods: Bioinformatics analysis and clinical sample evaluation were used to assess Ppih mRNA expression in HCC and its association with pathological features, immune infiltration, immunotherapy response, and patient prognosis. Additionally, we collected 40 serum samples from HCC patients and healthy controls to verify the secretion levels of PPIH, IFN-γ, granzyme B, and IgG. Results: This study demonstrated that Ppih mRNA levels were significantly elevated in HCC and were associated with poor prognosis. Ppih is strongly linked to the immune cell infiltration environment in HCC, where it can induce immune barriers and contribute to poor prognosis. Moreover, elevated serum PPIH levels were confirmed in patients with liver cancer. Conclusions: Our findings suggest that Ppih is a promising prognostic and immunotherapeutic marker for HCC. Its secreted protein may also serve as a potential serum biomarker, offering new insights into the role of Ppih and its interaction with the tumor immune microenvironment in HCC.